Concepcoes estratigraficas em analise de bacias: C) a estratigrafia genetica - Gama, E. (My University, 1989)
The present work fits the concepts of depositional systems and depositional sequence as paralithostratigraphic and parachronostratigraphic units, respectively, and discusses the advantages of using this approach in environmental reconstructions. The depositional system concept came to a focus as a link between sedimentology and stratigraphy since it represents both a facies association and a mapping unit. Additionally, the depositional sequence represents the sedimentary episode of relative sea level change, in interaction with basin paleophysiography. In such a way a time-space diagnosis is reached in environmental interpretation as illustrated by the Permian-Carboniferous sequence of the Parana Basin. -English summary
Stratigraphic approaches to basin analysis: c) the genetic stratigraphy
Keywords: Carboniferous; depositional system; environmental reconstruction; Permian; stratigraphy; Brazil, Parana Basin